The Role of Village Government in Cleaning Public Services at Petisah, Medan, Indonesia - Hadi Wahyudi Harahap; Humaizi Humaizi; Abdul Kadir (Budapest International Research and Critics University, 2018)
This study aims at describing and summarizing various conditions, various situations, or various phenomena of social reality that exist in life of society which are objects in this research and try to attract that reality to the surface so that it can be seen how social reality actually exists and is happening in life of society. This research was conducted in the Petisah Tengah Village, Medan Petisah village, Medan, North Sumatra Province. The researcher chose this village as the research location because of the diverse plurality of the people and the high level of socio-political dynamics because in this village there was the Medan Mayor's Office, as well as some government offices and Regional House of Representatives (DPRD) in Medan. This study used descriptive qualitative method. The type of research used by researchers in this study is a qualitative approach with descriptive studies. Qualitative research is a research procedure that produces description data in the form of words (both written and oral). This qualitative research method was chosen because it can present directly the nature of the relationship between researchers and respondents and is more sensitive and can adjust to the patterns of value faced. Data collection is done by observation and interview. The results of the study are more emphasized in giving an objective description of the actual state of the object under investigation, using a qualitative approach, the researcher will obtain more in-depth information or data.